Metagenomic profiling of microbial metal interaction in Red Sea deep-anoxic brine pools - Hanna, Mina Magdy Abdelsayed (AUC Knowledge Fountain, 2015)
Extreme environmental conditions induce evolution of microbiomes and shape microbial abundance. Different geochemical studies reported high metal abundance in Red Sea deep-anoxic brine pools, especially in Atlantis II Deep, which has the highest metals content. Brine pools show wide diversity of biologically essential and non-essential metals. Several metals known for their toxicity to biological life were detected in these pools. Yet, previous microbiome analyses of the pools demonstrated vast microbiological diversity. In this study, we compare metal-resistant prokaryotic microbiomes in different metal-rich brine water samples from Atlantis II lower convective layer (ATII-LCL), Atlantis II upper convective layer (ATII-UCL), Discovery Deep (DD) and Kebrit Deep (KD). Moreover, we investigate genome evolution of microbial communities in response to such excessive metal abundance. Using 16S rRNA pyrotags and shot-gun 454-pyrosequencing, we perform a comparative analyses of (i)-taxonomic assignment of operational taxonomic units to major bacterial and archaeal groups and (ii)-metal resistant protein-coding genes, of the microbial communities and metagenomes. The ATII-LCL, ATII-UCL, DD and KD brine pools metagenomes protein-coding genes involved in microbial-metal interaction and resistances were assessed for abundance and diversity. We report specific microbial richness of these three brine pools. Functional analyses of the metagenomes revealed different metal resistance mechanisms and different modes of mutual interaction between dissolved metals/sediments and microbial communities. This was supported by the strong correlation between specific high metal/s concentration in selected brine water, where; metal resistance, enrichment of metals metabolism and transport were revealed. As expected, ATII-LCL showed the highest relative abundance of genes involved in microbial-metal interaction. Additionally, we report significant abundance of peroxidases-encoding genes, mainly in ATII-LCL, and we hypothesize that generation of hydrogen peroxide (H2O2) occurs through interaction of pyrite deposits. Moreover, we suggest that genus Paenibacillus, which is highly abundant in ATII-LCL has a role in increasing concentration of dissolved iron in brine water. DD and KD showed relatively lower enrichment of genes involved in microbial-metal interaction. However, geochemistry of these environments together with unique microbial abundance give an inference about mechanisms of microbial metal interaction and metabolism taking place there. Eventually, we successfully identified free living metal-resistant prokaryotic communities, showed how prokaryotes tolerate and induce changes to the surrounding environment, and highlighted how geochemical conditions affected microbial abundance and induced evolution of microbiomes in brine pools.